2018
DOI: 10.3389/fmicb.2018.00663
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of DNA Repair in Infection Mediated-Inflammation and Cancer

Abstract: Pathogenic and commensal microbes induce various levels of inflammation and metabolic disease in the host. Inflammation caused by infection leads to increased production of reactive oxygen species (ROS) and subsequent oxidative DNA damage. These in turn cause further inflammation and exacerbation of DNA damage, and pose a risk for cancer development. Helicobacter pylori-mediated inflammation has been implicated in gastric cancer in many previously established studies, and Fusobacterium nucleatum presence has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 167 publications
(179 reference statements)
1
40
0
Order By: Relevance
“…One of the major sources of oxidative DNA damage in the colon is the disbalance of bacterial communities. Bacterial infection-induced inflammation leads to the generation of reactive oxygen species (ROS) that can result in oxidative damage, which is more prominent, especially with bacteria causing chronic infection (24). Bacterial species that play a role in the pathogenesis of CRC include Bacteroides fragilis, Helicobacter pylori, Escherichia coli, Enterococcus faecalis, and Clostridium septicum (71,72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major sources of oxidative DNA damage in the colon is the disbalance of bacterial communities. Bacterial infection-induced inflammation leads to the generation of reactive oxygen species (ROS) that can result in oxidative damage, which is more prominent, especially with bacteria causing chronic infection (24). Bacterial species that play a role in the pathogenesis of CRC include Bacteroides fragilis, Helicobacter pylori, Escherichia coli, Enterococcus faecalis, and Clostridium septicum (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli Nei-like (NEIL1-3) proteins are a distinct family of DNA glycosylases that remove both purines and pyrimidines. They initiate the excision of lesions present in a single-stranded region, a replication fork, or transcription bubble mimic (23)(24)(25)(26)(27)(28). Reduced expression of NEIL1, NEIL2, and elevated expression of NEIL3 is involved in the progression of several types of cancer via their association with the somatic mutation load (29).…”
Section: Introductionmentioning
confidence: 99%
“…Like TBK1, ATM and CHK2 were also predicted to be upregulated in all three IBP infections, both of which are activated under conditions of DNA damage. Activation of the host DNA damage could be the result of increased oxidative stress generated by NADPH oxidase (Sahan et al, 2018), which itself was ubiquitylated during infection ( Figure 1 E, CY24B). Surprisingly, several cyclindependent kinases (CDK1, CDK2, CDK4, CDK7) were downregulated with all three IBPs, indicating that infection led to cell cycle arrest.…”
Section: Global Phosphorylation Analysis Identifies Pathways Commonlymentioning
confidence: 99%
“…Generally, the bacterial infection-induced inflammation leads to the generation of reactive oxygen species (ROS) that in turn cause oxidative genome damage in the host cells. Without timely repair, the mutagenic DNA lesions can cause several pathologies, including cancer (10)(11)(12)(13). Oxidized DNA bases are primarily repaired via the DNA Base Excision Repair (BER) pathway (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Several other groups and we then found that mammalian cells possess a new family of DNA glycosylases, and named them E. coli Nei-like (NEIL1-3). NEILs are capable of removing both purines and pyrimidines; however, these DGs are unique with respect to DNA damage recognition, as OGG1 and NTH1 remove the damage from duplex DNA, whereas NEILs prefer to initiate excision of lesions that are located in a single-stranded region, a replication fork or transcription bubble mimic (13,23,24). Indeed, it was found that NEIL1 and NEIL3 are mostly involved in repairing the damage in replicating cells, and NEIL2 primarily removes the oxidized DNA bases from the transcribed regions (24).…”
Section: Introductionmentioning
confidence: 99%